MXene-Based Materials for Multivalent Metal-Ion Batteries - Wang, Chunlei; Pan, Zibing; Chen, Huaqi; Pu, Xiangjun; Chen, Zhongxue (Batteries (Basel), 2023)
Multivalent metal ion (Mg2+, Zn2+, Ca2+, and Al3+) batteries (MMIBs) emerged as promising technologies for large-scale energy storage systems in recent years due to the abundant metal reserves in the Earth’s crust and potentially low cost. However, the lack of high-performance electrode materials is still the main obstacle to the development of MMIBs. As a newly large family of two-dimensional transition metal carbides, nitrides, and carbonitrides, MXenes have attracted growing focus in the energy storage field because of their large specific surface area, excellent conductivity, tunable interlayer spaces, and compositional diversity. In particular, the multifunctional chemistry and superior hydrophilicity enable MXenes to serve not only as electrode materials but also as important functional components for heterojunction composite electrodes. Herein, the advances of MXene-based materials since its discovery for MMIBs are summarized, with an emphasis on the rational design and controllable synthesis of MXenes. More importantly, the fundamental understanding of the relationship between the morphology, structure, and function of MXenes is highlighted. Finally, the existing challenges and future research directions on MXene-based materials toward MMIBs application are critically discussed and prospected.